2017
DOI: 10.1080/15374416.2017.1342545
|View full text |Cite
|
Sign up to set email alerts
|

The Under- and Over-Identification of Autism: Factors Associated With Diagnostic Referral

Abstract: As reported prevalence and public awareness of Autism Spectrum Disorder (ASD) have grown in recent years, clinicians will likely see increased referrals for suspected ASD. The current study sought to elucidate factors associated with referral for possible ASD, as well as diagnostic outcome among youth referred for suspected ASD. Youth referred for psychological evaluations at an outpatient clinic (N = 69, 6-18 years, 48 male) were categorized into four groups: referred for suspected ASD and diagnosed as such, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Baghdadli et al [29] remarquent aussi que ces outils construits sur la base d'hypothèses catégoriques, appliquées à des phénotypes autistiques prototypiques, risquent de fixer un seuil de diagnostic trop élevé par exemple pour les adultes sans déficience intellectuelle, mais surtout pour les jeunes filles [80] et les femmes adultes [81], pour les sujets âgés [82] et pour les enfants en très bas âge [82,83] et présentant un phénotype sévère associé à un retard du développement intellectuel [65], ainsi que pour des individus enfants et adultes issus de cultures différentes (par ex., [84]). À l'inverse, un seuil peut être trop bas, dans d'autres circonstances, ce qui conduit à des faux-positifs [85].…”
Section: Limites De La Combinaison De L'adi-r Et De L'adosunclassified
“…Baghdadli et al [29] remarquent aussi que ces outils construits sur la base d'hypothèses catégoriques, appliquées à des phénotypes autistiques prototypiques, risquent de fixer un seuil de diagnostic trop élevé par exemple pour les adultes sans déficience intellectuelle, mais surtout pour les jeunes filles [80] et les femmes adultes [81], pour les sujets âgés [82] et pour les enfants en très bas âge [82,83] et présentant un phénotype sévère associé à un retard du développement intellectuel [65], ainsi que pour des individus enfants et adultes issus de cultures différentes (par ex., [84]). À l'inverse, un seuil peut être trop bas, dans d'autres circonstances, ce qui conduit à des faux-positifs [85].…”
Section: Limites De La Combinaison De L'adi-r Et De L'adosunclassified
“…Indeed, one study on the prevalence of final diagnoses of ASD among children (aged 1-19 years) referred to a regional diagnostic autism center revealed that only 61% met ASD diagnosis criteria [21]. Children who were referred for ASD evaluation and did not receive an ASD diagnosis were more frequently diagnosed with attention deficit hyperactivity disorder (ADHD) [21][22][23] and had more co-occurring diagnoses of developmental disorders and medical problems [23]. Other frequent alternative diagnoses included language disorder, disruptive behavior disorder/oppositional defiant disorder, intellectual disability, and anxiety disorder, with most children having multiple diagnoses [21].…”
Section: Introductionmentioning
confidence: 99%
“…Other frequent alternative diagnoses included language disorder, disruptive behavior disorder/oppositional defiant disorder, intellectual disability, and anxiety disorder, with most children having multiple diagnoses [21]. Studies that have sought to identify characteristics that may help to distinguish between those who will be diagnosed with ASD and those who will not, have shown that children who receive ASD diagnoses are characterized by lower cognitive ability [23], more severe RRB [22], and poorer abilities in the social communication domain, as determined by professionals [24].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for this complexity was given by Kentrou et al (2019), who showed that the delayed autism diagnosis with co-occurring ADHD stretched out a further year when the child was female in comparison with male children with autism + ADHD. The more complex a diagnostic picture, and the less typical symptom profile, the more difficult the diagnosis (Avlund et al, 2020;Smith et al, 2019).…”
Section: Discussionmentioning
confidence: 99%